THE ROLE OF FINANCIAL SECURITY OF ENTERPRISES IN COUNTERING THREATS AND RISKS - MARCHENKO, Valentyna; USYK, Oleksandr (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The purpose of the article is to highlight the role of financial security of enterprises in countering threats and risks in modern conditions. The relevance of the study is due to the fact that the modern realities of Ukraine’s development, taking into account the military invasion of its territory by the Russian Federation, actualize efforts in the direction of security in all spheres of life, including in relation to the financial security of enterprises. Threats and risks to the functioning of enterprises as a result of military actions on the territory of Ukraine are identified, which include physical destruction or damage to production premises, warehouses, infrastructure, which lead to the shutdown of enterprises, interruptions in the supply of raw materials, components and electricity, loss and outflow of personnel, changes in demand , caused by military actions and their consequences, problems of a logistical nature due to the destruction of infrastructure facilities, increased financial risks, legal risks, loss of foreign partners, increased cyber threats, reduced work capacity and employee motivation. External and internal threats and risks of enterprise activity are determined. As well as internal threats and risks of the financial activity of enterprises, which include: low level of staffing of financial activities; low level of financial responsibility at the enterprise; irrational capital management; insufficient use of financial risk management tools; low resource potential and adaptive capacity of the enterprise. It has been proven that the financial security of enterprises plays an important role in countering threats and risks, ensuring the stability and sustainability of the enterprise’s activities in conditions of uncertainty. The role of financial security in the system of economic security and enterprise activity involves: protection from financial and credit risks; increasing the efficiency of operational risk management; increasing investment stability.